Influence of Leadership To Satisfaction of Employee Affect to The Performance of Employee At Department of Management Market of Surakarta (Dinas Pengelolaan Pasar Pemkot Surakarta) - Ahmed A., Muhammed; , Drs. M. Farid Wajdi, MM., Ph.D; , Drs. Anton Agus Setyawan, SE., M.Si (2014)
The purpose of this study is to analyze the influences of leadership to satisfaction of employee at Department of Management Market of Surakarta, to analyze influence leadership to satisfaction of employee effect to the performance of employee at Department of Management Market of Surakarta, and to analyze the positive influences of leadership directly through the performance of employee at Department of Management Market of Surakarta (DINAS Pengelolaan Pasar PEMKOT Surakarta). Research conducted a descriptive study using a quantitative approach, by taking samples at Department of Management Market of Surakarta (DINAS Pengelolaan Pasar PEMKOT Surakarta), Central Java, Indonesia. The study population was all employees and staff of the Department of Management Market of Surakarta and samples taken by 50 employees. The technique of collecting data using questionnaires. The data analysis technique used is path analysis. The results obtained showed that: Leadership will influence on satisfaction of employee at Department of Management Market of Surakarta, satisfaction of employees affects the employee's performance of employees at Department of Management Market of Surakarta, and leadership influence on performance of employee indirectly through satisfaction of employees at Department of Management Market of Surakarta (DINAS Pengelolaan Pasar PEMKOT Surakarta).